Neither Peace nor War—U.S.-Cuban Political Coexistence from 1963 to 1964 - Krzysztof Siwek (European Journal of American Studies)
The purpose of this study is to examine the circumstances of the political coexistence of the United States with Cuba following the Cuban Missile Crisis and preceding the full U.S. engagement in Vietnam. The article reveals that the Cold War conditions of U.S.-Cuban- Soviet interdependence determined the international credibility of the United States and led to the U.S.-Cuban political stalemate. A political coexistence of the two states, under managed conditions of neither peace nor war, assured the benefits of reasonable security and long-term international credibility as well as political identity to both the United States and Cuba.